PERAN KEPUASAN KONSUMEN DALAM MEMEDIASI PENGARUH WOM TERHADAP LOYALITAS PELANGGAN KEDAI KOPI M ABOE TALIB - Dwinanda Putra, Dewa Bagus Ariesetyadi; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2022)
Despite the modern coffee shops' growth, the legendary M Aboe Talib coffee shop is always full of consumers. The coffee shop has entered its third generation of ownership. The bustling coffee shop founded in 1940 has attracted researchers to conduct research. This study aims to explain the effect of word of mouth on loyalty mediated by customer satisfaction. This research took place in the cities of Tabanan and Denpasar. The number of samples is 112 respondents taken with a non-probability sampling technique with the purposive sampling method. Data collection was obtained through a questionnaire. The analysis technique used is Path using SPSS software. Based on the results of hypothesis testing, word of mouth has a significant positive effect on consumer satisfaction. Better positive communication from consumers will produce better customer satisfaction and vice versa. Consumer satisfaction has a significant positive effect on loyalty by means better customer satisfaction will form high customer loyalty. Also, the more positive word of mouth, the higher customer satisfaction and will make customers loyal. The mediation effect that occurs in this study is partial mediation or partial mediation. Keyword : word of mouth, customer satisfaction, customer loyalty